The dyer's handbook : memoirs on dyeing - Cardon, Dominique (Ancient textiles series ;, 2016)
A translation and facsimile reproduction of a unique 18th century French manuscript that provides colour recipes and samples for producing dyes for the textiles of the day. With analysis and essays setting it in context.